The Properties of Rough Submodule over Rough Ring - Rahmawati, Rara Gusti; Fitriani, Fitriani; Faisol, Ahmad (Department of Matematics, Universitas Padjadjaran, 2024)
A pair of non-empty set U and equivalence relation R on U, denoted as (U,R), is called approximation space. Furthermore, equivalence classes form the construction of lower approximation and upper approximation. Let XU, the lower approximation of X denoted by X and the upper approximation of X denoted by X. A pair Apr(X)=(X,X) is a rough set if X≠ X. Apr(X) is rough module if Apr(X) satisfies some conditions. In this research, we investigate some characteristics of the rough module and rough submodule over rough ring. Furthermore, we construct examples of the rough module and the rough submodule on approximation space (U,R).